Study Of Land & Water Body Quality In Dalli-Rajhara Region: Remote Sensing And GIS Applications (International Journal of Environmental Sciences, 2024)
The present study investigates the spatial and temporal variations in land and water body quality (L&WBQ) in the Dalli-Rajhara region of Balod District, Chhattisgarh, employing Remote Sensing (RS), Geographic Information System (GIS), and field-based analyses. Multi-temporal Landsat and Sentinel datasets (2000–2024) were processed to derive indices such as NDVI, BSI, LST, NDWI, MNDWI, Turbidity Index (TI), and Suspended Sediment Index (SSI), which were integrated with field-based Water Quality Index (WQI) data. The analysis reveals that forest and agricultural land decreased by 37.5% and 24%, respectively, while mining and waste land expanded by 150% over 25 years. NDVI declined by 38%, reflecting vegetation loss, whereas LST rose by 3.6°C, indicating surface heating and land exposure. Water indices demonstrated a 65% reduction in NDWI and a twofold rise in turbidity indices, confirming sedimentation and hydrological degradation. Field analyses showed elevated iron (1.45 mg/L), BOD (6.5 mg/L), and turbidity (18 NTU) levels exceeding BIS/WHO limits. The integrated Composite Land and Water Body Quality Index (LWBQI) classified 45% of the study area as “Poor” to “Degraded,” primarily surrounding active mines and overburden dumps. The findings underscore the cumulative impacts of open-cast mining on ecosystem degradation and emphasize the potential of RS-GIS integrated frameworks for sustainable environmental monitoring, restoration, and policy formulation in mining regions.